Contemporary issues in development : essays in honour of Q.K. Ahmad - Ahmad, Qazi Kholiquzzaman, 1943-; Biswas, Asit K.; Brichieri-Colombi, J. S.A.; Chowdhury, Amirul Islam; Sajjadur Rasheed, K.B.; Bangladesh Unnayan Parishad; Third World Centre for Water Management (Dhaka : Bangladesh Unnayan Parishad ; Estado de México : Third World Centre for Water Management ; Dhaka : Academic Press and Publishers, 2002)
Contributed articles on diverse issues relating to social and economic development of Bangladesh.
Includes bibliographical references.
Includes statistical tables.
Keywords: Bangladesh -- Social conditions; Bangladesh -- Economic conditions; Bangladesh -- Social conditions -- Statistics; Bangladesh -- Economic conditions -- Statistics